The book of noble character : critical edition of Makārim al-aklāq wa-maḥāsin al-ādāb wa-badāʼiʻ al-awṣāf wa-gharāʼib al-tashbīhāy, attributed to Abū Manṣūr al- Thaʻālibī (d. 429/1039) (Islamic History and Civilization, 2015)
This critical Arabic text edition of K. Makārim al-akhlāq wa-maḥāsin al-ādāb wa-badāʾiʿ al-awṣāf wa-gharāʾib al-tashbīhāt ( Book of Noble Character, Excellent Conduct, Admirable Descriptions, and Curious Similes ) is a substantial work of adab attributed to the prominent littérateur Abū Manṣūr al-Thaʿālibī (d. 429/1039) that consists of a short introduction and three chapters. The first chapter addresses acquiring noble character and excellent conduct ( al-taḥallī bi-makārim al-akhlāq wa-maḥāsin al-ādāb ); the second addresses shunning away from base character and ugly traits ( al-tazakkī ʿan masāwiʾ al-akhlāq wa-maqābiḥ al-shiyam ); and the third addresses admirable descriptions and curious similes ( badāʾiʿ al-awṣāf wa-gharāʾib al-tashbīhāt ). At the end of the text one finds a relatively large collection of widely circulating proverbs ( amthāl sāʾira ) that are alphabetically arranged. Makārim al-akhlāq is in essence an anthology of "good conduct" and of quotations suitable for social and literary discourse. It reflects the three ingredients of adab : behavior, literary culture, and learning. The work is introduced by an analytical study discussing the attribution of the work, the related genres, and the unique manuscript of the text.